2004
DOI: 10.1097/01.alc.0000125347.93779.81
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Aminopeptidase Activity in Urine: A New Marker of Chronic Alcohol Abuse?

Abstract: The results of this study demonstrate that the assays of urinary AAP activity, which relate to the nephrotoxic effects of alcohol abuse, could be a valuable complement to the other presently used markers of chronic alcohol abuse that are generally based on ethanol hepatotoxicity. Compared with the uAAP activity test, the eAAP activity test is of clear diagnostic advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Moreover, the AUC was only negligibly greater for eHex than for uHex (one-tailed significance level, ps0.24), whereas it was significantly greater for eAAP than for uAAP (ps0.021). These results showed no substantial benefit from the Sephadex filtration step for the Hex assay, while the reverse was true for the AAP assay wsee also Taracha et al (24)x. Therefore, we decided to omit the eHex and uAAP results in further data analyses.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, the AUC was only negligibly greater for eHex than for uHex (one-tailed significance level, ps0.24), whereas it was significantly greater for eAAP than for uAAP (ps0.021). These results showed no substantial benefit from the Sephadex filtration step for the Hex assay, while the reverse was true for the AAP assay wsee also Taracha et al (24)x. Therefore, we decided to omit the eHex and uAAP results in further data analyses.…”
Section: Resultsmentioning
confidence: 81%
“…We have recently reported that uAAP is a good marker of chronic alcohol abuse, particularly after removing its endogenous inhibitors (24). While uncommon in clinical practice, uHex also has been Brought to you by | University of Arizona Authenticated Download Date | 6/5/15 8:35 PM Table 3 Diagnostic accuracy of the proposed compound marker G&Hs0.62=ln(GGT)q0.72=ln(uHex) and its component markers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations